Molecular evolution of human immunodeficiency virus type 1 upon transmission between human leukocyte antigen disparate donor-recipient pairs. - Marjon Navis; Diana Edo Matas; Andrea Rachinger; Fransje A Koning; Peter van Swieten; Neeltje A Kootstra; Hanneke Schuitemaker (PLoS ONE, 2008)
BACKGROUND: To address evolution of HIV-1 after transmission, we studied sequence dynamics in and outside predicted epitopes of cytotoxic T lymphocytes (CTL) in subtype B HIV-1 variants that were isolated from 5 therapy-naive horizontal HLA-disparate donor-recipient pairs from the Amsterdam Cohort Studies on HIV-1 infection and AIDS. METHODOLOGY/PRINCIPAL FINDINGS: In the first weeks after transmission, the majority of donor-derived mutations in and outside donor-HLA-restricted epitopes in Gag, Env, and Nef, were preserved in the recipient. Reversion to the HIV-1 subtype B consensus sequence of mutations in- and outside donor-HLA-restricted CTL epitopes, and new mutations away from the consensus B sequence mostly within recipient-HLA-restricted epitopes, contributed equally to the early sequence changes. In the subsequent period (1-2 years) after transmission, still only a low number of both reverting and forward mutations had occurred. During subsequent long-term follow-up, sequence dynamics were dominated by forward mutations, mostly (50-85%) in recipient-HLA-restricted CTL epitopes. At the end of long-term follow-up, on average 43% of the transmitted CTL escape mutations in donor-HLA-restricted epitopes had reverted to the subtype B consensus sequence. CONCLUSIONS/SIGNIFICANCE: The relatively high proportion of long-term preserved mutations after transmission points to a lack of back selection even in the absence of CTL pressure, which may lead to an accumulating loss of critical CTL epitopes. Our data are supportive for a continuous adaptation of HIV-1 to host immune pressures which may have implications for vaccine design.